Risk Factors for Drug Resistance in Epileptic Children with Age of Onset above Five Years: A Case-Control Study - Irawan Mangunatmadja; Raden Muhammad Indra; Dwi Putro Widodo; Achmad Rafli (Behavioural Neurology)
Background. Children with epilepsy with onset above five years encompass distinct epidemiological and clinical characteristics that may have specific risk factors for resistance to antiseizure medications (ASMs). Studies on this age group are limited. Purpose. To identify risk factors for drug resistance in children with epilepsy with the age of onset above five years. Methods. A case-control study was conducted on children with epilepsy with the age of onset above five years visiting the Pediatric Neurology Clinic of Cipto Mangunkusumo and Mohammad Hoesin Hospital between September 2015 and August 2016. Cases consisted of drug-resistant children while control consisted of drug-responsive children according to 2010 ILAE classification. Risk factors studied include onset, number of seizures, illness duration before treatment, cause, seizure type, status epilepticus, initial and evolution of EEG, brain imaging, and initial treatment response. Results. Thirty-two pairs of children were included in the study. After logistic regression analysis, symptomatic etiology and failure to achieve early response to treatment were found to be associated with drug resistance with adjusted OR of 84.71 (95% CI: 5.18-1359.15) and 72.55 (95% CI: 7.08-743.85), respectively. Conclusion. Poor initial response to ASM and symptomatic etiology are independent risk factors for drug resistance in children with epilepsy with the age of onset above five years.